Determinants of Treatment Success Among Drug Resistant Tuberculosis Patients in West Sumatra, Indonesia: a Retrospective Cohort Study (2017–2021) - Widoyo, Ratno; Djafri, Defriman; Triana, Vivi; Salsabila, Anisa (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2026)
Treatment success rates remain below the national target in Indonesia. This study aims to identify individual characteristics and health facility-level factors associated with treatment success among Drug-resistant tuberculosis (DR-TB) patients in West Sumatra. A retrospective cohort study encompassing DR-TB patients treated in West Sumatra between 2017 and 2021 was undertaken. Univariate, bivariate, and multivariate analyses are used to evaluate the association between facility-level factors, individual characteristics, and treatment outcomes. The analysis indicated a heightened propensity for successful treatment among male patients and those within younger age cohorts. Patients treated in district-level hospitals were more likely to achieve successful treatment outcomes than those treated in city-based hospitals. Furthermore, patients referred from other facilities to a different district hospital had significantly higher odds of success than those who received care at a single facility throughout their treatment. Younger Age, male gender, district hospital, and patients referred for DR-TB are likely to achieve treatment success. Besides individual characteristics, decentralized care and structured referral systems need improvement. Consequently, the prioritization of inter-facility coordination reinforcement and the augmentation of district hospital capacities are imperative within provincial tuberculosis control strategies.